Analysis of Training Models at LKP Course & IIN Sewing House, Jati Makmur, Binjai City - Adilla, Diva Ayu; Aulia, Annisa Khalikah; saragih, Putri Amelia; Sirait, Wilma Winanda; Rahma, Yulia; Hasibuan, Jubaidah (Universitas Negeri Jakarta, 2023)
The purpose of this research is to find out and analyze how the training model used in LKP Courses & Sewing Houses IIN is implemented. The type of research used in this research is qualitative research. The place of this research was conducted on Jl. Nibung 1 No. 9, Jati Makmur, Kec. North Binjai, Binjai City, North Sumatra. As for the data collection method with interview techniques and documentation techniques. Data analysis techniques were carried out using descriptive techniques. The research results show that 1). LKP Course & Sewing House IIN is a training institution that implements sewing training programs, 2). LKP Course & IIN sewing house in its application uses a deductive training model, 3). LKP Course & Sewing House IIN in its application conveys 30% theory and 70% practice, 4). LKP Course & Sewing House IIN based on the process and training material using a work skills training model.